The Portsmouth peace Treaty of 1905 in assessment of British ruling elite, diplomacy and press - I. V. Tsyganova (Омский научный вестник: Серия "Общество. История. Современность")
The article attempts to identify the positions of the members of the political elite, diplomacy and the press of Great Britain in connection with the signing of the Portsmouth Peace Treaty, which ended the Russian-Japanese war of 1904 – 1905. The author draws attention to that the peace process in Portsmouth was influenced by the signing of the Second Anglo-Japanese Union Treaty. Based on the study of parliamentary and diplomatic documents, materials of the British and Russian press, it is concluded that the British ruling circles are interested in signing peace between Japan and Russia, as well as the debatable assessment of the content of the articles of the Portsmouth Treaty and its impact on international relations in the Far East